MAPPING AND DESCRIPTION OF THE DISTRIBUTION OF TOURISM OBJECT AREAS IN THE TANJUNG SUB-DISTRICT, NORTH LOMBOK REGENCY - Muhammad Mujahid Dakwah; Abdurrahman Abdurrahman (Jurnal Ilmiah Hospitality, 2023)
The purpose of this research is to analyze, map and describe tourist attractions in improving and facilitating tourists in visiting and policy making by stakeholders, because one of the focuses of national economic development is in the tourism sector, while maintaining the nation's personality and environmental sustainability. The tourism sector provides many advantages or benefits, including being able to create jobs, increase and equalize community income, and introduce regional cultural arts and crafts to be marketed to domestic and foreign tourists. Ten tourist sites in Tanjung Sub-district were mapped to help inform the placement of tourist attractions. This map can also be used as a guide when listing tourist attractions and evaluating the potential of popular tourist destinations. Data descriptions of the tourist attractions in Kecamatan Tanjung, including location, tourist attractions, condition of facilities and infrastructure, condition of visitor numbers, and efforts to develop tourist attractions, show that the current level of tourism in the area has very good prospects. These tourist destinations generally have potential and if worked on properly will increase Regional Original Income (PAD) significantly. Mapping and description of the distribution of tourist attraction areas in Tanjung Sub-district, North Lombok Regency, West Nusa Tenggara is the most important part of decision-making by stakeholders for sustainable tourism development.